Formulasi Mie Kering Bahan Dasar Ikan Kembung dan Bayam Hijau sebagai Pangan Balita Stunting - Maria Magdalena Fetowin; Melanie Christine Kamo; Nurhayati Prinanda Putri Embisa; Sarah Petronela Demena; Nia Budhi Astuti (Pusat riset dan Inovasi Nasional, 2025)
Stunting remains one of the major nutritional problems in Indonesia. According to the 2024 Indonesian Health Survey (SKI), the prevalence of stunting in Papua Province reached 16.8%. A child’s nutritional status is strongly influenced by dietary intake, particularly protein, which plays a crucial role in growth. One potential source of animal protein is Indian mackerel (Rastrelliger kanagurta), a type of fish commonly found in Papua. Indian mackerel is rich in protein and omega-3 fatty acids but is highly perishable, limiting its shelf life. To address this issue, the fish is processed into flour. Additionally, green spinach is used as a source of fiber and minerals, although it is also prone to spoilage. The spinach is processed by extracting its juice, which is then incorporated into noodle products. Dried noodles were chosen as a medium for fortification because they are widely consumed across age groups and often used as a substitute for rice.This study aimed to determine the effect of adding Indian mackerel flour and green spinach extract on the chemical properties and sensory acceptance of dried noodles. The research methods included nutritional content analysis and organoleptic testing. The sensory evaluation was conducted by 25 semi-trained panelists who were nutrition science students